Increased Potency and Decreased Elimination of Lamifiban, a GPIIb-IIIa Antagonist, in Patients with Severe Renal Dysfunction - Lehne, Gustav; Nordal, Knut P.; Midtvedt, Karsten; Goggin, Timothy; Brosstad, Frank (Thrombosis and Haemostasis, 1998)
Activation of the platelet membrane receptor glycoprotein (GP) IIb-IIIa is essential for thrombus formation. The novel nonpeptide GPIIb-IIIa antagonist, lamifiban, represents a promising approach for antiplatelet therapy in patients with cardiovascular disease. Since renal impairment frequently occurs in these patients, we designed a phase I study to assess the tolerability, pharmacodynamics and pharmacokinetics of lamifiban in patients with renal impairment. Four healthy volunteers (Group 1) with creatinine clearance (CLCR) >75 ml/min, eight patients (Group 2) with mild to moderately impaired renal function (CLCR 30-74 ml/min) and eight patients (Group 3) with severe renal impairment (CLCR 10-29 ml/min) were studied. They received stepwise increased doses of lamifiban intravenously (IV). There was a linear relationship between the systemic clearance of the drug and renal function (R2 = 0.86). The mean plasma concentration required for half-maximal inhibition of thrombin-receptor agonist peptide (TRAP) induced platelet aggregation (EC50) ex vivo was 21, 28 and 11 ng/ml in Groups 1, 2 and 3. The patients in Group 3 were sensitized to the anti-platelet effect allowing an 18-fold dosage reduction without compromising the pharmacodynamics. In conclusion, the decreased clearance of lamifiban may act in concert with increased potency of the drug in patients with severe renal impairment, and the drug dosage should be reduced accordingly.